Determinants of Fraud Pentagon Theory Perspective and Its Effects on Fraudulent Financial Statement in Mining Companies Which Is Listed In Indonesia Stock Exchange - Heny Triastuti K; Sri Rahayu; Zenni Riana (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
This type of research is quantitative research. This study uses secondary data from financial statements and company annual reports published by the Indonesia Stock Exchange (IDX) during 2016-2018. The sampling technique uses a purposive sampling stage. Data analysis was performed using logistic regression analysis using SPSS version 22 software program which described the relationship between Financial Targets, External Pressure, Quality of External Auditors, Change in Auditors, Changes of Directors, and Frequent Number of CEO's Picture as an independent variable on the dependent variable, Fraudulent Financial Statement. The results of this study are Financial Target, External Pressure, Quality of External Auditor, Change in Auditor and The Board Directors has no effects on Fraudulent Financial Statement. The for Frequent Number of CEO’s Picture effect on Fraudulent Financial Statement.